Diversity, role in decomposition, and succession of zoosporic fungi and straminipiles on submerged decaying leaves in a woodland stream - Marano, Agostina Virginia (2011)
Leaf litter is a very important primary source of energy in woodland streams. Decomposition of leaf litter is a process mediated by many groups of microorganisms which release extracellular enzymes for the degradation of complex macromolecules. In this process, true fungi and straminipiles are considered to be among the most active groups, more active than the bacteria, at least during the early stages of the process. Colonization increases the quality of the leaves as a food resource for detritivores. In this way, matter and energy enter detritus-based food chains. Previously, aquatic hyphomycetes were considered to be the major fungal group responsible for leaf litter decomposition. Although zoosporic fungi and straminipiles are known to colonize and decompose plant tissues in various environments, there is scant information on their roles in leaf decomposition. This study focuses on the communities of zoosporic fungi and straminipiles in a stream which are involved in the decomposition of leaves of two plant species, Ligustrum lucidum and Pouteria salicifolia, in the presence of other groups of fungi. A characteristic community dominated by Nowakowskiella elegans, Phytophthora sp., and Pythium sp. was found. Changes in the fungal community structure over time (succession) was observed: terrestrial mitosporic fungi appeared during the early stages, zoosporic fungi, straminipiles, and aquatic Hyphomycetes in early-to-intermediate stages, while representatives of the phylum Zygomycota were found at early and latest stages of the decomposition. These observations highlight the importance of zoosporic fungi and straminipiles in aquatic ecosystems.